Elemen Visual Mitologi Cirebon dalam Perancangan Kerajinan Gerabah Sitiwinangun untuk Produk Interior - Almantara, Hatif Adiar; Winata, Gita; Yana, Deni (Serat Rupa: Journal of Design, 2024)
Since Sitiwinangun has announced as a pottery tourism village in 2016, various pottery development programs in this village have been initiated by several parties, including academics, government, and business entities. This research aims to develop a tradition of making pottery in Sitiwinangun with a focus on the potential of Sitiwinangun pottery, especially sculptures with the theme of Cirebon mythology that applied to the design of pottery products for interiors. The method used in this study is practice-led research through a design approach, a technical approach, and a visual approach with the stages of observation, design development, and design finalization. The results showed that the form of Cirebon's mythological sculptures could be developed through application to interior products. This research is to improve people's appreciation of local traditions, scientific development, product diversification, and the community's living standards and economy, especially in the pottery sector.